Proliferation and Apoptosis in H. Pylori-associated Chronic Gastritis with Epithelial Metaplasia - Zhumabaevna, Saule Akhmetova; Rsalievich, Abdiraman Kaliev; Balkashevna, Anarzhan Tulyaeva; Bulatovna, Aigul Ramankulova; Amirkhanqyzy, Talshyn Nurulla; Kozhakhmetovich, Nurbek Azbergenov; Meirimovna, Nurgul Kereeva; Zalimovich, Sergei Chukov (West Kazakhstan Medical Journal, 2025)
Helicobacter pylori - causes pathologies such as gastritis, peptic ulcer disease, adenocarcinoma. Pseudopyloric mucosal metaplasia in the incisura region is significantly correlated with the development of precancerous changes - atrophy and intestinal metaplasia. Pseudopyloric metaplasia of the gastric mucosa develops as a result of persistence of H. pylori infection. Immunohistochemical and histological study of gastric mucosa biopsy specimens from patients with dyspeptic complaints was performed. Chronic non-atrophic gastritis was histologically detected in 21 patients. Of these, 17 (80.95%) were H. pylori-positive. Out of 55 patients with chronic atrophic gastritis, 38 (69.1%) were H. pylori-positive. Ki-67 IM was significantly increased during the development of atrophic gastritis: in the antral region to 50.6±8.3 (P<0.05), in atrophy and pseudopyloric metaplasia in the incisura region to an average of 47.3±8.2 (P<0.05) and in the gastric body region to an average of 46.9±7.4 (P<0.05). In chronic atrophic gastritis, p53 expression was detected in the antral region in 22 (40.0%) patients, and in atrophy and pseudopyloric metaplasia in the incisura region in 18 (50.0%) and in the body in 4 (57.1%). All patients were H. pylori-positive. Intestinal metaplasia was found in 36 (65.5%) patients in the antral region, 34 (61.8%) patients in the incisura region and 24 (43.6%) patients in the body of the stomach This study showed that in chronic H. pylori-associated atrophic gastritis there is an acceleration of cell proliferation and impaired apoptosis, especially in areas of atrophy, as well as pseudopyloric and intestinal epithelial metaplasia, leading to an increased risk of gastric cancer.